2017
DOI: 10.1007/s40520-016-0700-9
|View full text |Cite
|
Sign up to set email alerts
|

Pain severity and pharmacologic pain management among community-living older adults: the MOBILIZE Boston study

Abstract: Background Concerns about polypharmacy and medication side effects contribute to undertreatment of geriatric pain. This study examines use and effects of pharmacologic treatment for persistent pain in older adults. Methods The MOBILIZE Boston Study included 765 adults aged ≥70 years, living in the Boston area, recruited from 2005 to 2008. We studied 599 participants who reported chronic pain at baseline. Pain severity, measured using the Brief Pain Inventory (BPI) severity subscale, was grouped as very mild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 42 publications
3
26
0
6
Order By: Relevance
“…This is important against the background of the history of chronic pain and intensity of current pain as observed during the last 24 hours in our cohort of patients. According to the MOBILIZE Boston study [33], about 30% of community-living older adults with moderate to severe pain were also inadequately treated, while 50% did not receive any pain medication [33]. The latter finding might be explained by the relative high ratio of patients with very mild to mild pain enrolled in this study [33].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This is important against the background of the history of chronic pain and intensity of current pain as observed during the last 24 hours in our cohort of patients. According to the MOBILIZE Boston study [33], about 30% of community-living older adults with moderate to severe pain were also inadequately treated, while 50% did not receive any pain medication [33]. The latter finding might be explained by the relative high ratio of patients with very mild to mild pain enrolled in this study [33].…”
Section: Discussionmentioning
confidence: 90%
“…According to the MOBILIZE Boston study [33], about 30% of community-living older adults with moderate to severe pain were also inadequately treated, while 50% did not receive any pain medication [33]. The latter finding might be explained by the relative high ratio of patients with very mild to mild pain enrolled in this study [33]. Roy et al reported in agreement with our current findings, that 16% of institutionalized elderly patients with pain did not receive treatment with analgesics [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Вероятно, у пациентов пожилого возраста чаще имеется структурная патология позвоночника (дегенеративные изменения позвонков и МПД, остеофиты, остеоартрит фасеточных суставов и др. ), что способствует хронизации воспаления и боли и снижает эффективность обезболивающих средств [18][19][20].…”
Section: Patients and Methods A Study Group Consisted Of 2078 Patienunclassified
“…Inappropriate prescriptions [97][98][99][100] and potential prescription omissions [98] have also been documented. Moreover, multiple medications are frequently used in patients with PTSD and traumatic brain injury [101,102], as well as in the management of chronic pain [103][104][105][106].…”
Section: Dietary Supplements and Nutraceuticals: Friends Or Foes?mentioning
confidence: 99%